SoftHM: A Software-Based Hierarchical Modulation Design for Wireless System - Chen, Weiwei; Liu, Yunhuai; He, Tian (IEEE/ACM transactions on networking, 2021)
Hierarchical Modulation (HM) is quite efficient for multimedia broadcast in wireless networks. It exploits the wireless broadcast advantage and allows a transmission to reach different users with various qualities. However, existing HM related schemes are based on specially designed hardware, leading to extra hardware and deployment cost in practice. As a remedy for this, we design and implement a software-based HM scheme, named as SoftHM. By carefully tuning the Physical Layer input of a packet (a sequence of "0" or "1" bits, known as PHY payload), a transmitter simply broadcasts the packet with a single rate (e.g., 54Mbps, the highest rate in 802.11g WLAN), while diverse receivers can decode and extract different amount of information (with different reception rate, e.g., 12Mbps or 54Mbps) from it based on their link qualities. Reverse engineering techniques are adopted so that SoftHM works in a plug-in mode, offering it high potentials for wireless systems without any changes in existing modulation and coding modules. We implement SoftHM based on Universal Software Radio Peripheral (USRP) B210 and Commercial of the Shelf (COTS) Wi-Fi devices. Both rigorous analysis on its performance and comprehensive implementation-based experiments show that compared with the traditional time-sharing approach, to support low-quality users with the same bandwidth, high-quality users in SoftHM achieve 111.1% to 616.7% higher throughput. Likewise, to serve high-quality users with the same bandwidth, low quality users in softHM achieve 176.9% to 390.9% higher throughput.